Bibliometric analysis of atmospheric simulation trends in meteorology and atmospheric science journals - Li, Jingfeng (Array, 2009)
Summary:This study was designed to evaluate the global scientific output of simulation research in meteorology and atmospheric sciences for the past 16 years and to assess the characteristics of the atmospheric simulation research patterns, tendencies and methods in the papers, from leading countries and institutes. Data were based on the online version of Science Citation Index, Web of Science from 1992 to 2007. Articles referring to atmospheric simulation were assessed by exponential regression fitting the trend of publication outputs with r2 = 0.9996, distribution of source countries, source institutes, source titles, author keywords, and keywords plus, and the four most cited articles in these years. By synthetic analysis of the three kinds of keywords, it was concluded that atmospheric simulation research related to ozone, climate, circulation, transport, parameterization and assimilation will be foci of atmospheric simulation research in the 21st century